2019
DOI: 10.1002/jum.15081
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Viscosupplementation: Ultrasound‐ Versus Landmark‐Guided Injection for Knee Osteoarthritis

Abstract: Objectives-Viscosupplementation, intra-articular injection of hyaluronic acid (HA), for knee osteoarthritis has fallen somewhat out of favor, with studies failing to show consistent benefits in pain reduction. Hyaluronic acid must enter the joint space to be beneficial; however, landmark-guided injection can be substantially inaccurate, especially in obese patients. We aimed to determine whether ultrasound (US) guidance to ensure needle placement for HA knee injection resulted in improved outcomes as reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…It is hypothesised that non-animal derived HA is associated with decreased rates of allergic response and pseudoseptic arthritis and our results support this [ 1 , 18 , 22 ]. The use of ultrasound guidance also reduces the negative outcomes of misplaced injection [ 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that non-animal derived HA is associated with decreased rates of allergic response and pseudoseptic arthritis and our results support this [ 1 , 18 , 22 ]. The use of ultrasound guidance also reduces the negative outcomes of misplaced injection [ 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…19-22 27 28 32 55 In one retrospective cohort study with high RoB, an even worse outcome for US versus palpation-guided injection was found with a higher percentage of patients requiring an additional knee reinjection with hyaluronic acid in the US group (20.3% vs 15%, respectively). 18 In the palpation-guided group, however, more patients received an additional GC injection (34% vs 27.4%, respectively). In another study, it was observed that patients with knee osteoarthritis and US-guided injection had a worse quality of life at 3 months than patients with palpation-guided injections, while walking and standing tests were better in the former than in the latter group.…”
Section: Efficacymentioning
confidence: 93%
“…US guidance improved injection accuracy and clinical outcomes at 6-and 12-week follow-up compared with palpation-guided injections in a randomized trial [24]. Long-term, precise intra-articular injection of HA by US guidance was associated with a reduced knee arthroplasty rate compared to the palpation-guided approach, particularly in obese patients [25,32].…”
Section: Us-guided Ha Intra-articular Injections Are Safe and Improve Pain Scores And Function In Knee Osteoarthritis Showing Greater Effmentioning
confidence: 93%
“…Randomized trials comparing US-guided and palpation-guided corticosteroid intra-articular injections [17,22] reported pain reduction at 2-week follow-up, 107% increase in the responder rate, and 36% increase in therapeutic duration with subsequent cost reduction, using US guidance [22]. In knee osteoarthritis treated with HA injections, the use of US guidance resulted in enhanced functional and pain-score improvement after 6 and 12 weeks [24], with long-term decreased knee arthroplasty rate [25] when compared to palpation guidance. In emergency settings, both blind and US-guided arthrocentesis were successful, although the latter led to higher volume aspiration for novice practitioners [26].…”
Section: Level Of Evidencementioning
confidence: 99%